2012
DOI: 10.1111/sjop.12022
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of electroencephalographic frontal alpha asymmetry and frontal midline theta as biomarkers for depression

Abstract: Electroencephalographic (EEG) frontal alpha asymmetry (FAA) and frontal midline (FM) theta have been suggested as biomarkers for depression and anxiety, but have mostly been assessed in small and non-clinical studies. In a clinical sample of 79 adults with depression (ICD-10: F32), resting EEG and scales of depression (MADRS) and anxiety (HADS-A) were measured at intake and after 3 months. FAA and FM theta values were referenced to a normative population database. Internal consistency, test-retest reliability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 47 publications
3
73
0
Order By: Relevance
“…EEG alpha asymmetry has been investigated as a biomarker for MDD with a decreased alpha power at right frontal sites relative to the left side [82,83,84,85,86], although many studies have failed to replicate these findings [81,87,88,89,90,91]. Interestingly in ADHD, Keune et al [92] found the opposite pattern of alpha asymmetry with increased right frontal alpha power.…”
Section: Biomarkersmentioning
confidence: 94%
“…EEG alpha asymmetry has been investigated as a biomarker for MDD with a decreased alpha power at right frontal sites relative to the left side [82,83,84,85,86], although many studies have failed to replicate these findings [81,87,88,89,90,91]. Interestingly in ADHD, Keune et al [92] found the opposite pattern of alpha asymmetry with increased right frontal alpha power.…”
Section: Biomarkersmentioning
confidence: 94%
“…These training protocols consisted of amplitude uptraining and/or downtraining of selected frequency bands based on qEEG findings. Protocol selections were based on current research and reflect markers found to be associated with anxiety issues (Dantendorfer et al, 1996;Demerdzieva & Pop-Jordanova, 2011;Gold, Fachner, & Erkkilä, 2013;Gunkelman, 2006;Gurnee, 2000;Heller, Nitschke, Etienne, & Miller, 1997;Johnstone, Gunkelman, & Lunt, 2005;Machleidt, Gutjahr, Muegge, & Hinrich, 1985;Price & Budzynski, 2009;Savostyanov et al, 2009;Siciliani, Schiavon, & Tansella, 1975;Stern, 2005, p. 196;Tharawadeepimuk & Wongsawat, 2014;Walker, 2009 Note. Combined sites = two 10/20 sites adjacent to selected 10/10 site.…”
Section: Protocolsmentioning
confidence: 99%
“…interhemispheric electrode pairs and depressive symptoms measured using the Montgomery and Asberg Depression Rating Scale (MADRS) (Gold et al, 2013). Similar results were found in a small sample of older participants (>65 years old) including depressed (n=12), remitted (n=8) and control subjects.…”
Section: Depression and Alpha Asymmetrysupporting
confidence: 70%
“…Frontal alpha asymmetry was not significantly associated with depressive symptoms in 79 adults with DSM-IV diagnosed (Gold et al, 2013). A mild but nonsignificant positive correlation was found between frontal alpha asymmetry in F7-F8…”
Section: Depression and Alpha Asymmetrymentioning
confidence: 67%